2021
DOI: 10.1021/jacs.1c01404
|View full text |Cite
|
Sign up to set email alerts
|

Productive Alkyne Metathesis with “Canopy Catalysts” Mandates Pseudorotation

Abstract: Molybdenum alkylidyne complexes of the “canopy catalyst” series define new standards in the field of alkyne metathesis. The tripodal ligand framework lowers the symmetry of the metallacyclobutadiene complex formed by [2 + 2] cycloaddition with the substrate and imposes constraints onto the productive [2 + 2] cycloreversion; pseudorotation corrects this handicap and makes catalytic turnover possible. A combined spectroscopic, crystallographic, and computational study provides insights into this unorthodox mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(78 citation statements)
references
References 39 publications
8
69
0
Order By: Relevance
“…[ 17 , 22 , 23 ] Combined spectroscopic, crystallographic and computational studies unveiled the unorthodox mechanism by which such “canopy catalysts” operate as a consequence of the geometric constraints imposed onto the reactive intermediates by the tripodal silanolate ligand sphere. [ 24 , 25 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 17 , 22 , 23 ] Combined spectroscopic, crystallographic and computational studies unveiled the unorthodox mechanism by which such “canopy catalysts” operate as a consequence of the geometric constraints imposed onto the reactive intermediates by the tripodal silanolate ligand sphere. [ 24 , 25 ]…”
Section: Introductionmentioning
confidence: 99%
“…The Lewis acidity of the W(+6) center in 5 is upregulated to the extent that the catalytic turn‐over ceases. [ 24 , 25 , 26 ] Therefore, a fundamentally different ligand design had to be pursued: [26] complex 6 with an expanded tris‐alkoxide (rather than siloxide) chelate ligand framework constitutes a promising new lead in that it outperformed a classical Schrock catalyst of type 7 (R=2,6‐dimethylphenyl),[ 27 , 28 , 29 , 30 ] although it still does not rival the best molybdenum catalysts known to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This exigent transformation worked again very nicely, independent of whether the in situ catalyst mixture ( 29 / 30 ) 56 or the structurally defined canopy catalyst 31 ( 33 35 ) was used. The need for fairly high loadings is again tentatively ascribed to the forcing conditions necessary to override the incipient ring strain of the polycyclic product 70 , which certainly also accelerate catalyst decomposition (for reaction optimization, see the SI ); this notion is supported by recent results from our laboratory.…”
Section: Resultsmentioning
confidence: 75%
“…Gratifyingly, we found that the newly developed and molecularly well-defined molybdenum alkylidyne complex 31 distinguished by a tripodal silanolate ligand sphere is at least equipotent. 33 35 Although a fairly high loading and rather forcing conditions proved necessary to overcome the strain of the incipient tetracyclic scaffold, cycloalkyne 28 was obtained in 83% yield on a 1.3 g scale (for reaction optimization, see the Supporting Information (SI)); its constitution and stereostructure were unambiguously established by 2D NMR spectroscopy and X-ray diffraction ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%